EURO-MUSCULUS/USPRM Dynamic Ultrasound Protocols for Wrist and Hand - Mezian, Kamal; Ricci, Vincenzo; Güvener, Orhan; Jačisko, Jakub; Novotny, Tomas; Kara, Murat; Ata, Ayşe Merve; Wu, Wei-Ting; Chang, Ke-Vin; Stecco, Carla; Pirri, Carmelo; Leblebicioğlu, Gürsel; et al. (American journal of physical medicine & rehabilitation, 2022)
In this dynamic protocol, ultrasound evaluation of the wrist and hand is described using various maneuvers for relevant conditions. Scanning videos are coupled with real-time patient examination videos. The authors believe that this practical guide-prepared by the international consensus of several experts-will help musculoskeletal physicians perform a better and uniform/standard examination approach.
Keywords: muskuloskeletální systém; Ultrasonography; Physical and Rehabilitation Medicine; muskuloskeletální nemoci; zápěstí; ruka; Musculoskeletal Diseases; lidé; rehabilitační lékařství; Wrist; Musculoskeletal System; Hand; Humans; ultrasonografie